Influência da unidade de luz, tempo de fotoativação e sistema de polimento na rugosidade superficial de resinas compostas - Bueno, Cheyenne Coscia (2021)
Objective: To evaluate the influence of LED light curing units, curing time and polishing system on the surface roughness of two composite resins. Materials and methods: The composite resins evaluated were Vit-l-escence and Tetric N-Ceram. Eight samples, 2mm thick and 4mm in diameter, were prepared for each group. The samples were light cured for 10 or 40 seconds using a Bluephase G2 or VALO Grand and stored in water distilled for 24 hours. After the storage period, the samples received surface treatment with Soflex disc. The polishing protocol was performed with Jiffy Polisher or A.S.A.P. The average surface roughness was measured with a roughness tester in three moments: initial, after application of Soflex disc and final. Results: The polishing system (p = 0,019) and type of curing unit (p = 0,0001) had an influence on this study. VALO promoted lower roughness values with a statistically significant difference for Bluephase G2. Regarding the Bluephase G2, the Vit-l-escence resin cured for 10 seconds showed a higher average roughness value when compared to Vit-l-escence cured for 40 seconds and Tetric N-Ceram cured for 10 seconds. Jiffy-VALO combination promoted the lowest values of roughness regardless of the composite resin and time used. The Vit-l-escence-10s-Bluephase-ASAP group had the highest average roughness (0.36 μm), differing statistically from the other groups. Conclusion: The light curing units and the type of polishing system can influence the surface roughness of both studied composite resins. The light curing with Bluephase G2 for 10 or 40 seconds promoted similar roughness in the composite resin Tetric N-Ceram regardless of the polishing system used. The Vit-l-escence composite resin showed the lowest surface roughness when cured with VALO for 40 seconds and polished with Jiffy Polisher.